Source-specific metabolic profiles and gene expression in areca nut cultivars from Hainan (China) - Sun, Yuanyuan; Feng, Jian; Liang, Haojie; Zhang, Shunan; Wu, Yuxia; Xie, Anzhen; Zeng, Lin; Liu, Yangyang (Frontiers in Plant Science, 2025)
Areca catechu L. are versatile plants whose fruits and seeds have great economic value. Although widely cultivated in Hainan Province, China, including native (HN) and introduced varieties from Taiwan (TW), Thailand (TG), and Vietnam (YN), the metabolic and regulatory differences among these varieties remain unclear. This study employed multi-omics techniques to analyze the metabolic profiles of phenylpropanoids, flavonoids, and alkaloids, along with their transcriptomic metabolic regulation, in the seeds of four areca nut germplasms. The research revealed significant metabolic differences among the seed varieties: the HN variety exhibited 175 differential metabolites, predominantly lignans, coumarins, and unsaturated fatty acids; the TW variety showed 270 differential metabolites with notably higher levels of flavonoids; the YN variety displayed 131 differential metabolites, characterized by intermediate overall metabolite levels but remarkably high glycerophospholipid content; and the TG variety contained 226 differential metabolites with relatively lower overall metabolite abundance. Furthermore, the key enzymes CCR and CHS were identified as core regulatory factors responsible for the differential accumulation of lignins, coumarins, and flavonoids observed between the HN and TW varieties. Overall, this study uncovers source-specific metabolic and regulatory distinctions in several AN varieties and provides further insights for enhancing AN utilization and supporting economic resilience for growers by identifying metabolites and biosynthetic pathways relevant to medicinal value and industrial processing.